Persepsi Siswa Terhadap Penggunaan Media Digital pada Pembelajaran Matematika Kelas 3 di MIN 4 Kebumen - Rika Mulyaningrum; Maryanto (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2026)
This study aims to describe the perceptions of third-grade students towards the use of digital media in mathematics learning. This study uses a descriptive qualitative approach. The main focus of this study covers three aspects: the use of digital media, students' learning interests, and students' perceptions towards the learning process involving technology. The study focused on one class, namely class IIIA (3 Sunan Kalijaga) at MIN 4 Kebumen. This study used data collection techniques through observation, interviews, and documentation. The data were analyzed interactively with the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of digital media such as the Math Learning Center and Spin Wheel can increase student interactivity and enthusiasm in mathematics learning. In addition, students showed a higher interest in learning when the material was presented using digital media because of its attractive and interactive display. Students' perceptions towards the use of digital media tend to be positive, because this media helps them better understand abstract concepts in mathematics more easily. This study concludes that the use of digital media not only increases interest and motivation to learn but also strengthens students' conceptual understanding.